Bolt-Grout Interactions in Elastoplastic Rock Mass Using Coupled FEM-FDM Techniques. (18th July 2010) - Deb, Debasis; Das, Kamal C.
Abstract : Numerical procedure based on finite element method (FEM) and finite difference method (FDM) for the analysis of bolt-grout interactions are introduced in this paper. The finite element procedure incorporates elasto-plastic concepts with Hoek and Brown yield criterion and has been applied for rock mass. Bolt-grout interactions are evaluated based on finite difference method and are embedded in the elasto-plastic procedures of FEM. The experimental validation of the proposed FEM-FDM procedures and numerical examples of a bolted tunnel are provided to demonstrate the efficacy of the proposed method for practical applications.